African Pentecostalism and the 1918 influenza pandemic: The supernatural amid the fearful and implications for the COVID-19 pandemic - Sneha Kirubakaran (Health for All Nations, 2020)
Infectious outbreaks that lead to epidemics and pandemics are dreaded because of the adverse health, economic, and social effects. The 1918 pandemic caused by the H1N1 influenza virus killed about 40 million people worldwide. Like the case of COVID-19, the pandemic of 1918 kept Christians, as well as people of other faiths, from worshipping together. However, African indigenous Pentecostal movements and groups emerged in various parts of the continent around the same time. This period was the time of huge Pneumatic experience and spiritual awakening. Pentecostals devoted themselves to building their faith and praying ceaselessly during that time, and this has become the foundation of the doctrine and theological instruction of most African-initiated churches (AICs). Because there have been no studies that consider the 1918 flu pandemic and Pentecostal response in Africa, this study was undertaken. The time of the 1918 pandemic appeared to be a good opportunity for spiritual awakening. Intense prayer prevailed during those times, and teaching and exposition about prayer formed the core of the theology of most AICs. Pandemics often bring devastation but could also be an opportunity for spiritual awakening through prayer, love in action, social justice, compassion, and care.